Polygonal graphics for the study of the correlation of statistical units: Gráficos poligonales para el estudio de la correlación de unidades estadísticas - Alfaro Alfaro, David A. (2022)
This article contains an analysis of correlations between multiple statistical units of a study, through the use of Polygonal Graphs, which are generated from an add-in created in Excel, where programming commands are used to filter the information creating the desired graph according needs. This approach is based on a new procedure, showing data analysis represented in polygons graphs, where the number of statistical units that coincide with the same characteristics of the analyzed variables. These results obtained, facilitate the analysis of metadata in statistical studies using a spreadsheet.